Determinants of Quality Antenatal Care in Pregnant Women Using NFHS-4 Data: A Path Analysis Approach - Sachit Ganapathy; Bhanushree Soni; Akash Mishra (Indian Journal of Community Medicine)
Introduction: Quality antenatal care (QANC) is an important health care indicator of the public health structure of the country. Causal mediation analysis is a statistical model that can model the complex path that determines the QANC received by women. The objective of the study was to assess the proportion of women receiving QANC in India and to ascertain its determinants using causal mediation analysis. Methodology: The dataset for study was obtained from the NFHS-4 survey. The outcome variable QANC was formulated based on a set working definition. The potential determinants of QANC at individual and population levels were identified by literature search, expert opinion, and availability in the NFHS dataset. The effect estimates of the determinants were estimated by multiple logistic regression. The potential determinant variables were categorized as independent and mediating variables. A schematic path analysis model was conceptualized by plausibility and expert opinion. The direct, indirect, and total effects of independent and mediating variables were estimated by generalized causal path analysis. Results: We found that region, education, wealth, religion, working status, husband’s education, and age were significant independent factors influencing QANC. Additionally, we found that husband’s alcohol status, pregnancy awareness month, presence of husband during antenatal care (ANC) visit, pregnancy registration month, emotional violence, and timing of the first ANC visit were significant mediating variables. Conclusion: Understanding the factors associated with QANC is statistically more robust using causal path analysis, which would help us better shape policies for improved maternal health care in India.